Oxidative Stress-Associated Male Infertility: Current Diagnostic and Therapeutic Approaches - Haritha Pavuluri; Zahra Bakhtiary; Manesh Kumar Panner Selvam; Wayne J. G. Hellstrom (Medicina, 2024)
Infertility is a prevalent global issue affecting approximately 17.5% of adults, with sole male factor contributing to 20–30% of cases. Oxidative stress (OS) is a critical factor in male infertility, disrupting the balance between reactive oxygen species (ROS) and antioxidants. This imbalance detrimentally affects sperm function and viability, ultimately impairing fertility. OS also triggers molecular changes in sperm, including DNA damage, lipid peroxidation, and alterations in protein expression, further compromising sperm functionality and potential fertilization. Diagnostic tools discussed in this review offer insights into OS markers, antioxidant levels, and intracellular ROS concentrations. By accurately assessing these parameters, clinicians can diagnose male infertility more effectively and thus tailor treatment plans to individual patients. Additionally, this review explores various treatment options for males with OS-associated infertility, such as empirical drugs, antioxidants, nanoantioxidants, and lifestyle modifications. By addressing the root causes of male infertility and implementing targeted interventions, clinicians can optimize treatment outcomes and enhance the chances of conception for couples struggling with infertility.